Private Sector Economic Impacts from Identification Systems - World Bank (World Bank, Washington, DC, 2019)
Identification systems are a core component of sustainable development policies in countries with diverse economic, demographic, and political contexts. The role of digital identification systems in the private sector is equally large. The efficient, accurate, and secure use of personal identity data is at the heart of most transactions, regardless of the industry in which they take place. The implementation of robust and inclusive identification systems at the national level offers the potential for large financial gains for private sector companies. As a companion piece to the World Bank’s identification for development (ID4D) work on fiscal savings for government agencies, this paper provides a first step toward developing a greater understanding of the financial benefits of identification systems for the private sector. By developing a framework for cost savings and revenue generation opportunities and aggregating existing case studies, it provides a preliminary assessment of expected benefits of government-backed identification systems for firms across a variety of industries. This paper is therefore intended to serve as a resource for governments and donors looking to gauge the potential impacts of implementing an identification system and for private sector leaders and industry groups to fruitfully engage on identity-related issues.